The Influence of the TAPPS (Thinking Aloud Pair Problem Solving) Learning Model on the Cognitive Abilities of Reaction Rate Material - Moh. Firmansyah Firmansyah; Kasmudin Mustapa; Ijirana Ijirana; Ratman Ratman (Journal of Educational Chemistry (JEC), 2025)
This research aims to determine the effect of the TAPPS (Thinking Aloud Pair Problem Solving) learning model on the cognitive abilities of class XI students in reaction rate material at SMA Negeri 1 Ampibabo. The population in this study were all students of SMA Negeri 1 Ampibabo, totaling 150 people consisting of 5 classes. This type of research is a type of quasi-experimental research with a research design using pretest and posttest experimental groups and control groups. Sampling was carried out based on purposive sampling with a research sample of XI IPA E totaling 35 students as the experimental class using the TAPPS learning model, XI IPA A totaling 35 students as the control class using the learning model conventional. Data collection techniques use test techniques. Based on the research results, it can be concluded that there is an influence of the TAPPS learning model on reaction rate material on students' cognitive abilities at SMA Negeri 1 Ampibabo. This is based on the results of calculations using the SPSS Version 25 application where the Sig value (2-tailed) = 0.029 < 0.05, then Ha is accepted and Ho is rejected, meaning that there is a significant influence between the use of the TAPPS learning model on reaction rate material on the cognitive abilities of class XI students in the Reaction Rate material at SMA Negeri 1 Ampibabo.